Multi-Level CO2 Injection Testing and Monitoring at the South West Hub In-Situ Laboratory. (November 2018) - Michael, Karsten; Avijegon, Arsham; Ricard, Ludovic; Dance, Tess; Piane, Claudio Delle; Freifeld, Barry; Woitt, Mark; Stalker, Linda; Myers, Jo; Peruvkhina, Marina; Langhi, Laurent; Hortle, Allison; et al.
Abstract: The In-Situ Laboratory Project entails completing, instrumenting and pump testing five intervals in an existing well and injecting a small volume of CO2 for testing purposes into the Lesueur Formation at the South West Hub project in Western Australia. The project commenced in the middle of October 2016 and is scheduled to run until the end of April 2019, with hydraulic testing and CO2 injection planned towards the end of 2018. The purpose is to aid demonstration of the commercial viability of geologically storing carbon and contribute to broadening the portfolio of globally evaluated geological settings for storage via testing of a more than 1000 m thick injection reservoir in which CO2 migration is largely governed by residual saturation and dissolution trapping. The project will develop the first part of an enduring research facility at the South West Hub to enable further research of a geological environment that has more uncertainty than many other current projects; i.e. in the case of the South West Hub there is uncertainty around the extent of a regional seal.